2019
DOI: 10.1002/ijc.32218
|View full text |Cite
|
Sign up to set email alerts
|

Prospective serum metabolomic profiling of lethal prostate cancer

Abstract: Impaired metabolism may play an important role in the pathogenesis of lethal prostate cancer, yet there is a paucity of evidence regarding the association. We conducted a large prospective serum metabolomic analysis of lethal prostate cancer in 523 cases and 523 matched controls nested within the Alpha‐Tocopherol, Beta‐Carotene Cancer Prevention (ATBC) Study. Median time from baseline fasting serum collection to prostate cancer death was 18 years (maximum 30 years). We identified 860 known biochemicals through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 43 publications
2
35
0
Order By: Relevance
“…In contrast, little is known about the association of lysophosphatidylcholines (treelet component 3) with risk of dying from prostate cancer. Another study in ATBC reported an inverse association between lysolipid 1‐linoleoyl‐glycerophosphatidylcholine (18:2), which is comparable to lysoPC a C18:2 included in TC3 of the current study, and risk of death from prostate cancer ( n deaths = 523), but death was not an outcome in the other previous papers.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…In contrast, little is known about the association of lysophosphatidylcholines (treelet component 3) with risk of dying from prostate cancer. Another study in ATBC reported an inverse association between lysolipid 1‐linoleoyl‐glycerophosphatidylcholine (18:2), which is comparable to lysoPC a C18:2 included in TC3 of the current study, and risk of death from prostate cancer ( n deaths = 523), but death was not an outcome in the other previous papers.…”
Section: Discussionsupporting
confidence: 56%
“…Previously, relatively small prospective studies ( n cases = 74–1,077), including our study in the European Prospective Investigation into Cancer and Nutrition (EPIC), showed that men with higher circulating concentrations of lipids and/or energy‐related metabolites might have lower risk of prostate cancer, especially more aggressive tumor subtypes . Moreover, a prospective study of lethal prostate cancer reported associations with metabolites in redox (inverse), dipeptide (positive), pyrimidine (mostly positive) and gamma‐glutamyl amino acid (positively) pathways ( n deaths = 523) . These studies mostly had limited power and have primarily investigated individual metabolites, which do not capture patterns in the metabolite profile reflecting correlations among metabolites; such patterns might represent metabolites which are part of the same metabolic pathway or originating from the same dietary sources .…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Subsequently, Huang et al conducted a large prospective serum metabolomic analysis of lethal prostate cancer in 523 cases and 523 controls [ 50 ]. Thirty-four serum metabolites were associated with death from prostate cancer.…”
Section: Resultsmentioning
confidence: 99%
“…In other unclear circumstances, the cause and mechanism of death can be explained by a novel research method that can be described as “metabolomics autopsy”, showing undiscovered pathophysiological mechanisms in different death causes. Metabolic profiling of post-mortal biological specimens may explain more deeply the pathogenesis of fatal disorders like cardiovascular disease [ 67 ], fatal cancers [ 68 , 69 ], diabetes mellitus [ 70 ], or traumatic brain injury [ 71 ]. On the other hand, important disturbances in selected metabolic pathways leading to changes in the concentration of the indicated metabolites may constitute a significant extension of the postmortem diagnosis, especially associated with stages of the disease.…”
Section: Applications Of Metabolomics In Forensic Medicinementioning
confidence: 99%